Experiences of maternity care in New South Wales among women with mental health conditions - L. Corscadden; E. J. Callander; S. M. Topp; D. E. Watson (BMC, 2020)
Abstract Background High quality maternity care is increasingly understood to represent a continuum of care. As well as ensuring a positive experience for mothers and families, integrated maternity care is responsive to mental health needs of mothers. The aim of this paper is to summarize differences in women's experiences of maternity care between women with and without a self-reported mental health condition. Methods Secondary analyses of a randomized, stratified sample patient experience survey of 4787 women who gave birth in a New South Wales public hospital in 2017. We focused on 64 measures of experiences of antenatal care, hospital care during and following birth and follow up at home. Experiences covered eight dimensions: overall impressions, emotional support, respect for preferences, information, involvement, physical comfort and continuity. Multivariable logistic regression was used to compare experiences of women with and without a self-reported longstanding mental health condition. Results Compared to women without a condition, women with a longstanding mental health condition (n = 353) reported significantly less positive experiences by eight percentage points on average, with significant differences on 41 out of 64 measures after adjusting for age, education, language, parity, type of birth and region. Disparities were pronounced for key measures of emotional support (discussion of worries and fears, trust in providers), physical comfort (assistance, pain management) and overall impressions of care. Most women with mental health conditions (75% or more) reported positive experiences for measures related to guidelines for maternity care for women with mental illness (discussion of emotional health, healthy behaviours, weight gain). Their experiences were not significantly different from those of women with no reported conditions. Conclusions Women with a mental health condition had significantly less positive experiences of maternity care across all stages of care compared to women with no condition. However, for some measures, including those related to guidelines for maternity care for women with mental illness, there were highly positive ratings and no significant differences between groups. This suggests disparities in experiences of care for women with mental health conditions are not inevitable. More can be done to improve experiences of maternity care for women with mental health conditions.